STRATEGI PEMBINAAN AKHLAK TERHADAP SANTRI DI PONDOK PESANTREN (Studi Kasus Ma’had Darul Istiqomah Padang Sidempuan) - Idawati Idawati; Lahmuddin Lubis; Wahyudin Nur Nasution (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This study aims to explain how the personality development of students through an Islamic counseling approach at the Ma'had Darul Istiqomah Islamic boarding school, Padang Sidempuan. As a formulation of the problem how to plan the personality development of students, the implementation of personality development of students, and how to evaluate the personality development of students. This type of research is a qualitative research with a phenomenological approach. Sources of field data are in the form of primary data and secondary data. Collecting research data using observation techniques, interviews and document studies. Data analysis techniques consist of data collection, data reduction, data presentation, and conclusions. The data validity techniques consist of credibility, transferability, dependability, and confirmability. The conclusions in this study are: first, the planning of student personality development consists of: identifying forms of student delinquency, factors causing student delinquency, efforts to handle student delinquency. Second, the implementation of student personality development through an Islamic counseling approach including: coaching the personality of students through moral development, congregational prayers, sunnah fasting, tadarus Qur'an and social activities. Third, the evaluation of the personality development of students includes cognitive, affective and psychomotor. Evaluation of the psychomotor domain is the part that gets the most attention in the personality development process because it is closely related to practice, namely the participation of students in carrying out personality development activities.